1997
DOI: 10.1177/088626097012004008
|View full text |Cite
|
Sign up to set email alerts
|

Self-Discrepancies in Young Adults and Childhood Violence

Abstract: Drawing on Higgins, Klein, and Strauman's (1985) self-discrepancy theory of anxiety and depression, we investigated the relation between violence in childhood and later discrepancies in young adults between their perceptions of their actual self and the self they felt they ought to be or would ideally like to be. Reports of early violence were significantly associated with actual-ought self-discrepancies, and also with perceived parental actual-ought discrepancies, but not with actual-ideal discrepancies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…This finding is consistent with previous studies that found a link between self-discrepancies in adulthood and a history of CSA (Brewin and Vallance 1997;Freshwater et al 2001), although these studies did not ask about gendered self-concept. It is also in line with research that has found elevated negative self-representations among abused female children and adolescents (e.g., Calverley et al 1994).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This finding is consistent with previous studies that found a link between self-discrepancies in adulthood and a history of CSA (Brewin and Vallance 1997;Freshwater et al 2001), although these studies did not ask about gendered self-concept. It is also in line with research that has found elevated negative self-representations among abused female children and adolescents (e.g., Calverley et al 1994).…”
Section: Discussionsupporting
confidence: 95%
“…Research has found abuse history related to actual-ought (Brewin and Vallance 1997) and actual-ideal (Freshwater et al 2001) self-discrepancies. However, no study has examined directly the link between CSA and particular aspects of the self, such as gender or feminine identity.…”
Section: Abuse and Stereotyping About Womenmentioning
confidence: 99%
“…For instance, a violent attack on an individual represents a failure of an implicit but fundamental prevention goal related to keeping the self safe from harm (Brewin & Vallance, 1997). Similarly, the sudden and unexpected loss of a job or spouse can result in perceived failures in fundamental promotion goals because of the roles that relationships and careers play in enabling people to make good things happen.…”
Section: Regulatory Focus and Psychopathology: Depression Versus Anxietymentioning
confidence: 99%
“…For example, exposure to community violence, peer victimization, and parental loss have each been associated with high levels of engagement in habitual rumination, a repetitive and passive cognitive response to dysphoric mood that involves focusing on the causes and consequences of negative affect (Heleniak et al 2015; McLaughlin et al 2009; McLaughlin and Hatzenbuehler 2009; Michl et al 2013; Wadsworth et al 2005). Stressful life events might increase engagement in rumination in adolescents because negative and unexpected life experiences serve as salient reminders of discrepancies between goals and reality, which increases attention to these discrepancies and rumination about how to resolve them (Brewin and Vallance 1997; Ferguson et al 2010; Papadakis et al 2006). …”
Section: Introductionmentioning
confidence: 99%